Cryptanalysis of RSA with Small Prime Difference. - De Weger, Benne (Applicable algebra in engineering, communication and computing.)
We show that choosing an RSA modulus with a small difference of its prime factors yields improvements on the small private exponent attacks of Wiener and Boneh-Durfee.